Density controlled conductivity of pristine graphene films - COLEMAN, JONATHAN (My University, 2013)
Single or few layer graphene can be considered an exciting pseudo-two-dimensional molecular material that potentially has a wide range of applications. A critical bottleneck may arise with issues in their controlled assembly into macroscopic ensembles over large areas both in two and three dimensions. Langmuir-type assembly is a particularly useful method to control and manipulate the distribution of graphene at the air–water interface via edge–edge interactions. In this study, pristine graphene suspended in organic solvent was prepared through adaptation of a previously developed process involving the non-invasive exfoliation of graphite. Successful deposition of graphene at the air–water interface was achieved by manipulating the vapor-pressure of the graphene dispersion through solvent mixing. Through careful control of density, by following the pressure-area isotherm during monolayer compression, it is possible to precisely tune the electrical conductivity. The resulting assemblies can be easily transferred to glass and other substrates using the Langmuir–Schaefer horizontal deposition method producing thin films with tunable electrical conductivity that exhibits percolation-type behavior. A major advantage of this process is that the conducting films require no further treatment unlike their graphene-oxide counterparts. Moreover, the physical properties of these assemblies can be easily controlled which is a precursor for graphene-based electronic applications.
PUBLISHED
Keywords: Graphene